2021
DOI: 10.1038/s41598-021-03677-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immune-related genes as prognostic biomarkers for the assessment of osteosarcoma clinical outcomes

Abstract: Cancer immunotherapy is a promising therapeutic approach, but the prognostic value of immune-related genes in osteosarcoma (OS) is unknown. Here, Target-OS RNA-seq data were analyzed to detect differentially expressed genes (DEGs) between OS subgroups, followed by functional enrichment analysis. Cox proportional risk regression was performed for each immune-related gene, and a risk score model to predict the prognosis of patients with OS was constructed. The risk scores were calculated using the risk signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…PLD3 can regulate inflammatory cytokine response through the degradation of nucleic acid. PLD3 has also been shown to be a prognostic protective gene for osteosarcoma, but this is the first time we have confirmed that it is also a B-cell marker gene for osteosarcoma (12)(13)(14). SNX2 belongs to the sorting nexin family and plays a role in the transport of intracellular cargo proteins.…”
Section: Discussionmentioning
confidence: 77%
“…PLD3 can regulate inflammatory cytokine response through the degradation of nucleic acid. PLD3 has also been shown to be a prognostic protective gene for osteosarcoma, but this is the first time we have confirmed that it is also a B-cell marker gene for osteosarcoma (12)(13)(14). SNX2 belongs to the sorting nexin family and plays a role in the transport of intracellular cargo proteins.…”
Section: Discussionmentioning
confidence: 77%
“…Gene expression can promote the migration and infiltration of specific immune cells, such as T cells or macrophages, into tumor tissue, often closely linked with patient prognosis. In osteosarcoma, analysis of immune-related gene expression identified key genes associated with disease progression and prognosis [30]. Similarly, in prostate cancer, gene expression significantly correlated with immune cell infiltration levels, particularly T-cells γδ, with important implications for understanding disease progression and personalized treatment strategies [31].…”
Section: Discussionmentioning
confidence: 99%
“…Filamin-C belongs to a family of three actin-binding proteins that stabilize actin networks and connect them to the cell membrane, with its silencing associated with cancer-increased invasiveness through the lamellipodia formation [ 35 ]. Pld3 represents an immune-related gene, with its low expression leading to a lower survival in patients with osteosarcoma [ 39 ]. This exonuclease (also named phospholipase D3) was recently found to be transcriptionally regulated by p53, with its higher expression representing a good prognostic factor in patients with pancreatic cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%